Technê e Eudaimonia a partir dos diálogos platônicos Protágoras, Górgias e República - Lima Junior, Elias de (2024)
This thesis is composed of three chapters. In the first, we address the development of the concept of technê, using the myth of Prometheus, both in Aeschylus and in Plato’s Protagoras, in order to compose the philosophical reflection on the advent of technology in Ancient Greece. In the second chapter, we address the problem of the moral conflict within the reflection on technology. That is, whether technology can be used only for good, or whether its practice allows for an ambiguous use, and can also be used for evil. To this end, we refer to the dialogues Protagoras, Gorgias and Book I of the Republic, where we follow Socrates in his clash against the sophists. In the third chapter, we address Socrates’ theses on technê, where we will find his explanation on the relationship between technology, good and happiness, in Book I of the Republic. We propose to find in Plato a philosophical doctrine on technology and human happiness